2022
DOI: 10.3389/fnut.2022.930949
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fermented dairy products is associated with lower anxiety levels in Azorean university students

Abstract: A growing number of studies have found that the gut microbiota is involved in a variety of psychological processes and neuropsychiatric disorders, which include mood and anxiety disorders. Consumption of dairy products may contain bioactive compounds and probiotic bacteria with various therapeutic benefits. The aim of the study was to investigate possible associations between the frequency of consumption of different types of dairy products and the state of anxiety in university students. The subjects were 311… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…There are only a few studies investigating the relationship between consumption of fermented foods and anxiety. Sousa et al ( 43 ) demonstrated that the consumption of fermented dairy products such as yogurt and cheese has a positive effect on reducing anxiety in Portuguese students. A prospective cohort study indicated that a positive association was found between the consumption of fermented food such as yogurt, kefir, and soured milk and severity of anxiety symptoms in Polish adults ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies investigating the relationship between consumption of fermented foods and anxiety. Sousa et al ( 43 ) demonstrated that the consumption of fermented dairy products such as yogurt and cheese has a positive effect on reducing anxiety in Portuguese students. A prospective cohort study indicated that a positive association was found between the consumption of fermented food such as yogurt, kefir, and soured milk and severity of anxiety symptoms in Polish adults ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 20.4% of Chinese adults consume dairy products at least once a week, and 68.5% of respondents reported they never or rarely consume dairy products [ 28 ]. Among college students in Azorean, 91.8% of female students and 98.8% of male students were reported to consume at least one serving of dairy products between two and four times per week [ 26 ]. The reason for this difference may be related to differences in the geographical dietary habits of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings are from studies of adults, and there is limited research on college student populations. A study from the Azores showed that the consumption of fermented dairy products had a positive effect on reducing anxiety in young college students [ 26 ]. In addition, probiotics have been reported to improve panic anxiety, neurophysiological anxiety, negative emotions, and worry, and to increase the regulation of negative emotions in college students [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, traditional fermented foods can be a source of novel microorganisms with interesting properties that can be utilised by the food industry [4][5][6]. In recent decades, there has also been increasing scientific evidence that fermented foods and the microorganisms associated with them can positively affect human health [7][8][9][10][11][12]. Certain microorganisms benefit the host by correcting imbalances in the gut microbiota [13,14], stimulating immunity [15] and producing a variety of bioactive compounds including vitamins [16], enzymes [17], bacteriocins [18], bioactive peptides [19], conjugates of linoleic acid (CLAs) [20], short-chain fatty acids [21], gammaaminobutyric acid (GABA) [22] and exopolysaccharides (EPSs) [23].…”
mentioning
confidence: 99%